Promising anti-Helicobacter pylori and anti-inflammatory metabolites from unused parts of Phoenix dactylifera CV 'Zaghloul': in vitro and in silico study - Nada Elhefni; Sherif S. Ebada; Marwa M. Abdel-Aziz; El-Sayed M. Marwan; Saleh El-Sharkawy; Mona El-Neketi (Taylor & Francis Group, 2023)
AbstractContext Date palm waste is an agricultural waste that accumulates in massive amounts causing serious pollution and environmental problems.Objectives Date palm trees, Phoenix dactylifera Linn CV 'Zaghloul' (Arecaceae) grown in Egypt, leave behind waste products that were investigated to produce compounds with anti-Helicobacter pylori and anti-inflammatory activities.Materials and methods Chromatographic workup of P. dactylifera aqueous methanol extract derived from fibrous mesh and fruit bunch (without fruit) afforded a new sesquiterpene lactone derivative, phodactolide A (1), along with ten known compounds (2-11), primarily identified as polyphenols. Chemical structures were unambiguously elucidated based on mass and 1D/2D NMR spectroscopy. All isolated compounds were assessed for their activities against H. pylori using broth micro-well dilution method and clarithromycin as a positive control. The anti-inflammatory response of isolated compounds was evaluated by inhibiting cyclooxygenase-2 enzyme using TMPD Assay followed by an in silico study to validate their mechanism of action using celecoxib as a standard drug.Results Compounds 4, 6 and 8-10 exhibited potent anti-H. pylori activity with MIC values ranging from 0.48 to 1.95 µg/mL that were comparable to or more potent than clarithromycin. For COX-2 inhibitory assay, 4, 7 and 8 revealed promising activities with IC50 values of 1.04, 0.65 and 0.45 μg/mL, respectively. These results were verified by molecular docking studies, where 4, 7 and 8 showed the best interactions with key amino acid residues of COX-2 active site.Conclusion The present study characterizes a new sesquiterpene lactone and recommends 4 and 8 for future in vivo studies as plausible anti-ulcer remedies.